Research on the construction of an evaluation index system of teachers’ online learning power based on online professional learning communities - Xiang, Lei; Yu, Liumei (Frontiers in Psychology, 2025)
IntroductionIn line with the overarching demands of the current educational ecological reform, online learning should transition from “novelty” to “normalization.” Teachers in elementary and secondary schools are currently learning in an active style that stresses the development of learning power, gradually moving away from a passive form. The efficiency and effect of teachers’ online learning are closely correlated with their level of online learning power. However, teachers’ professional development is limited and there is a lack of direction at the practical level of online learning because there is no efficient evaluation index system for teachers’ online learning power. Therefore, this study first conducts an in-depth study on the ELLI project learning power theory and the online learning power structure framework based on the attributes of the online professional learning communities (OPLCs), such as autonomy, professionalism, and openness.MethodsOn this basis, research methods including the Delphi method, the Analytic Hierarchy Process, and the questionnaire survey method are employed to study the evaluation dimensions of teachers’ online learning power. Establishing a scientific, logical, and operable index system for evaluating teachers’ online learning power is the aim. The OPLCs-based evaluation index system of teachers’ online learning power has been established following a series of studies that included the preliminary construction of the evaluation index system using the literature analysis method, the Delphi method for revision, the Analytic Hierarchy Process for determining the weights of each index item, and the questionnaire survey method for small-scale trial testing.ResultsThe evaluation index system consists of six first-level indicators and twenty-two second-level indicators. Furthermore, the evaluation index system’s dimension division and weight distribution are reasonable, well-scientific, and reliable.DiscussionThis research offers vital support and decision-making basis for effective diagnosis and precise improvement of teachers’ online learning power, and puts forward new requirements and action guidelines for teachers’ professional development.